1998
DOI: 10.1017/s0022112097008410
|View full text |Cite
|
Sign up to set email alerts
|

A universal time scale for vortex ring formation

Abstract: The formation of vortex rings generated through impulsively started jets is studied experimentally. Utilizing a piston/cylinder arrangement in a water tank, the velocity and vorticity fields of vortex rings are obtained using digital particle image velocimetry (DPIV) for a wide range of piston stroke to diameter (L/D) ratios. The results indicate that the flow field generated by large L/D consists of a leading vortex ring followed by a trailing jet. The vorticity field of the leading vortex ring formed is disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

143
952
18
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 961 publications
(1,144 citation statements)
references
References 16 publications
143
952
18
3
Order By: Relevance
“…The present numerical simulations of the formation of laminar vortex rings confirm the experimental and analytical findings of Gharib et al (1998) and extend them to additional cases, including cases with thick shear layers. For thin shear layers, the formation number is confirmed to be approximately equal to four for a wide range of cases differing in the discharge time (piston stroke ratio), velocity programme, generator configuration and Reynolds number.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present numerical simulations of the formation of laminar vortex rings confirm the experimental and analytical findings of Gharib et al (1998) and extend them to additional cases, including cases with thick shear layers. For thin shear layers, the formation number is confirmed to be approximately equal to four for a wide range of cases differing in the discharge time (piston stroke ratio), velocity programme, generator configuration and Reynolds number.…”
Section: Discussionsupporting
confidence: 81%
“…The finding of Gharib et al (1998) of the existence of a maximum in the circulation a vortex ring can acquire as the stroke ratio increases was also confirmed. A new finding of the present study is that the maximal vortex circulation (scaled by the maximal discharge velocity and the diameter of the orifice) is only weakly dependent on the discharge velocity profile or velocity programme.…”
Section: Discussionmentioning
confidence: 63%
“…where L is the length of a fluid slug ejected from the nozzle, D 0 is the nozzle diameter, U p is the average piston velocity and t p is the discharge time, as defined in Gharib, † Email address for correspondence: jodabiri@caltech.edu Rambod & Shariff (1998). This definition is based on the use of a piston-cylinder apparatus for producing vortex rings in a quiescent tank.…”
Section: Introductionmentioning
confidence: 99%
“…The formation time,t GRS , can be thought of physically as the non-dimensional piston travel distance (L) or alternatively as the non-dimensional pulse duration (t p ). Gharib et al (1998) demonstrated that vortex ring pinch off, a phenomenon where a forming vortex ring is kinematically separated from its trailing jet, occurs at a critical formation timet GRS ≈ 4. showed that for isolated vortex rings the pulse-averaged thrust normalized by the momentum flux is maximized at this critical formation time, known as the formation number F. Krueger, Dabiri & Gharib (2003 further showed that the formation number, F, can be reduced from its typical value of 4 when in the presence of coflow, such as that occurring in a self-propelled vehicle. Ruiz et al (2011) achieved significant increases in propulsive efficiency using vortex-enhanced propulsion, but did not explore the dependence of propulsive efficiency on vortex formation time.…”
Section: Introductionmentioning
confidence: 99%
“…Other patterns were also observed. Gharib, Rambod & Shariff (1998) proposed an alternative paradigm to predict optimal performance of unsteady biological propulsors based on the generation of vortex rings using a piston and cylinder. They identified the formation number n = L/D (L = piston stroke, D = diameter) such that for n ≈ 4 both the vortex ring circulation and the time-averaged force were maximized.…”
Section: Introductionmentioning
confidence: 99%